The Influence Of Green Perceived Value On Green Loyalty Through Green Satisfaction And Green Trust (Study On The Cosmetic Industry) - Ramadhan, Satria Putra; Aisjah, Siti (Jurnal Manajemen Indonesia, 2024)
The development of rapid industry cosmetics in Indonesia is driven by the increasing class medium and demand to produce beauty-friendly environments, pushing industry cosmetics To produce and develop more products in a friendly environment containing natural ingredients. In an era of increasingly strict competition, especially in consumer-oriented industries like cosmetics, companies often face challenges in maintaining customer loyalty. Effective strategies to awaken the loyalty of consumers are to make them trust and satisfy the products and actions of the company. To gain consumer trust and satisfaction, the company needs to pay attention to the value given. Research This will explain more Far with investigating the complex connection between mark perception green, satisfaction, trust and loyalty in the purchase and use of cosmetics based on a friendly environment. Research This was done against 170 respondents with the use of an approach through the distribution of an online questionnaire on Java Island. Data analysis methods use the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Research This discloses results that consider the perception of green, satisfaction, and trust positively and significantly related to a loyalty-friendly environment. In addition, it is also obtained that satisfaction and trust make mark perception green important, though satisfaction and trust only partly influence it. This confirms that without the existence of satisfaction and trust, loyal consumers of the cosmetics industry will find it difficult to wake up.